linta meliala,roito yuliana UJI EFEKTIVITAS ANTIDIARE EKSTRAK ETANOL DAUN GAGATAN HARIMAU (Vitisgracilis BL) PADA TIKUS JANTAN PUTIH - Meliala, Linta (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Abstract Diarrhea is the abnormal passage of loose or watery stools, with a frequency of more than three times a day. Diarrhea can be caused by bacteria. Gagatan Harimau leaves are known to have antibacterial properties. This research was conducted using an experimental method in the field of pharmacology at the Pharmacology Laboratory, Faculty of Pharmacy, Deli Husada Health Institute Delitua, using 25 rats induced with castor oil and divided into 5 treatment groups: negative control (1% CMC Na), positive control (Loperamide HCl), and treatment groups with ethanol extract of Gagatan Harimau leaves at doses of 50 mg/kg body weight (BW), 100 mg/kg BW, and 200 mg/kg BW. The sample used was Gagatan Harimau leaves (Vitis graillis BL), which were extracted by maceration using 96% ethanol as the solvent and concentrated using a rotary evaporator. The phytochemical screening results of Gagatan Harimau leaves showed the presence of flavonoids, saponins, alkaloids, and tannins. The results of the antidiarrheal effect test showed that the ethanol extract of Gagatan Harimau leaves at doses of 50, 100, and 200 mg/kg BW had antidiarrheal effects on male rats. The 200 mg/kg BW dose of ethanol extract showed the most effective antidiarrheal effect compared to the 50 and 100 mg/kg BW doses. The extract from Gagatan Harimau leaves (Vitis gracillis BL) exhibited antidiarrheal effects on male white rats induced with castor oil.